Discussion on Effect of Wind on Stroke Incidence and Course of Disease from Two Sanhua Decoction - Xinyun SONG; Motan QIU; bowen ZHAO Cheng; Jidong WANG (康复学报)
Stroke is a disease with high incidencerate, high mortality and high disability rate. Since ancient times, the record and treatment of stroke existed in China. Sanhua decoction is one of the famous prescription which used for the treatment of stroke. This article analyzes the two Sanhua decoction in ancient books and summarizes modern medicine theories, then tries to find a prescription analysis. The finding is that the same factor of wind was taken into consideration in the two Sanhua decoction, which may play a certain guiding significance for the treatment and prevention of modern stroke.